Immunotherapeutic potential of ethanolic olive leaves extract (EOLE) and IL-28B combination therapy in ENU induced animal model of leukemia. (August 2022) - Nath, Priyatosh; Majumder, Debabrata; Debnath, Rahul; Debnath, Mousumi; Singh Sekhawat, Surinder; Maiti, Debasish
Abstract: Cytokine therapies have shown promising results against cancers. Cytokines are secreted naturally from different bodily cells. These have fewer side effects but higher specificity than chemotherapy and radiation therapy. In leukemia, changes in normal hematopoiesis and defective leukocyte production limit the efficacy of immunotherapy by reducing the count of functional immune cells. Therefore, the treatment of leukemia needs advanced therapeutics that can target multiple cancer sustaining mechanisms. In combination therapy, using two different therapeutic agents affect cancer growth in many ways and sometimes gives synergistic effects. Here, we examined the effect of the ethanolic olive leaf extract (EOLE) and IL-28B in combination. N-N′ Ethyl-nitrosourea (ENU) induced leukemia in Swiss albino mice was treated with EOLE for four weeks and IL-28B for one week after confirming the development of leukemia. The combination of EOLE and IL-28B significantly reduced the blast cell and total WBC counts in the peripheral blood, altered the levels of various cytokines in plasma, and induced the functional activity of NK cells in leukemic mice. The induced NK activity correlates with increased expression of perforin and granzyme studied at the gene level through real-time (RT)-PCR. The treatment of leukemic mice with combined EOLE and IL-28B has also caused an increased serum IL-10 and IFN-γ level, and reduced serum TGF-β indicates improved overall immunity. Altogether, the combination of EOLE and IL-28B has given substantial therapeutic activity against leukemia.